Oxaliplatin-Based Platinum(IV) Prodrug Bearing Toll-like Receptor 7 Agonist for Enhanced Immunochemotherapy - Tang, Li (ACS Omega, 2019)
[Image: see text] A combination of platinum drugs with immunotherapy has shown promising anticancer effects, especially in the drug resistance cancer model. Herein, a new type of immunochemotherapeutic was designed by tethering the toll-like receptor 7 (TLR7) agonist on the axial position of oxaliplatin-based platinum(IV) prodrug. The prodrug simultaneously induced immunogenic cell death of 4T1 cancer cells to initiate an immune response and activate dendritic cells (DCs) to secrete proinflammatory cytokines including interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and IL-12, to further enhance the adaptive immunity. The prodrug exhibited better in vivo anticancer effects than oxaliplatin in the 4T1 allograft mouse model, a later stage breast cancer model, which showed poor response to traditional chemotherapy. Mechanism studies revealed that enhanced activation of cytotoxic T cells within tumor contribute to the high in vivo anticancer efficiency of the prodrug. Moreover, the prodrug displayed much lower cytotoxicity to DCs compared with oxaliplatin, indicating its safety to normal cells. These results highlight the potential of the conjugation of TLR7 agonist with oxaliplatin-based Pt(IV) prodrug as an effective anticancer agent to overcome the toxic side effects and drug resistance of traditional platinum chemotherapy.